The Influence of Leadership Style and Organizational Culture on Employee Loyalty With Work Satisfaction as an Intervening Variable - Wafa Nur’aeni; Sunardi Sembiring Brahmana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of leadership style and organizational culture on employee loyalty at PT Garment Sukabumi, with job satisfaction as an intervening variable. This study uses a quantitative approach with a survey method, involving 322 employees of PT Garment Sukabumi as respondents. Data were collected through a questionnaire that measured employee perceptions of leadership style, organizational culture, job satisfaction, and employee loyalty. Data analysis was carried out using multiple linear regression techniques and mediation tests. The results showed that leadership style and organizational culture had a positive and significant effect on employee loyalty, both directly and indirectly through job satisfaction as an intervening variable. In particular, job satisfaction was shown not to mediate the influence of leadership style and organizational culture on employee loyalty. This study provides an important contribution to understanding the factors that influence employee loyalty, especially in the context of manufacturing companies, and provides recommendations for the management of PT Garment Sukabumi to improve the quality of leadership style and organizational culture to motivate employees and increase their loyalty. These findings are expected to provide insight for other companies that want to strengthen the relationship between leadership style, organizational culture, and employee loyalty.